Construction Disaster Hazard Caused by a Defective Building Structural Survey - Kruszka, Leopold; Ostrowska, Alicja (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The present paper encompasses an analysis of a production hall reinforced concrete roof structure in terms of its limiting snow load. Errors which were made at the survey and thermal retrofitting design stages for the structure in question have been identified. These contributed to a construction disaster hazard which could occur in the event of intensive snowfall. Reinforced concrete roofing structures are least prone to failures caused by the impact of the weather, however they do occur.
Keywords: construction disaster; structural failure; structure diagnostics; snow load; roofing structure